A Preface to Mark : Notes on the Gospel in Its Literary and Cultural Settings. - Bryan, Christopher (Oxford University Press, 1997)
This study of Mark's Gospel aims to establish what kind of text it was seen to have been, by others and Mark himself, and to determine if it was written to be read aloud. The conclusions seek to place the Gospel in its original settings and enrich contemporary readings.